Improving Chilean In-Service Elementary Teachers’ Understanding of Nature of Science Using Self-Contained Nos and Content-Embedded Mini-Courses - Jimenez-Badaracco, J (Kluwer Academic Publishers, 2014)
Understanding nature of science (NOS) is considered critical to the development of students’ scientific literacy. However, various studies have shown that a large number of elementary and secondary science teachers do not possess an adequate understanding of NOS. This study investigated how elementary teachers’ understanding of NOS was impacted through a 1-year professional development program in Chile that included NOS instruction as a theme throughout two types of mini-courses in the program. Twelve teachers attended a 1-year development program focused on improving teacher content knowledge and included the instruction of NOS embedded in two self-contained NOS mini-courses (36 h) and two lessons (3 h each) within five science content mini-courses (30 h). The Views of NOS (version D+) questionnaire and interviews were used to assess teachers’ understanding of NOS at the beginning (January) and end of the program (December). Elementary teachers’ understanding of the creative, inferential, and tentative aspect of NOS showed improvement. According to the teachers’ perceptions, the most significant activities for improving their NOS understanding were decontextualized activities in both types of mini-courses (self-contained NOS and science content mini-courses). The implications for professional development programs are also discussed. © 2014, The Association for Science Teacher Education, USA.